2013
DOI: 10.1007/s13762-013-0425-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effects of exposure conditions on the biological responses of Gammarus pulex exposed to cadmium

Abstract: This study was conducted to determine the single and combined effects of cadmium (Cd) exposure at different concentrations and durations on biological responses in Gammarus pulex. The animals were exposed to 4, 8, 16 or 32 lg l -1 of CdCl 2 for 24, 48, 72 or 96 h, respectively. Cd accumulation, protein content, malondialdehyde content (MDA) and three antioxidant enzymes superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) were studied. The results were analyzed with two-way analysis of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Similar high sensitivity of GPx to trout farm pollution was observed in Gammarus dulensis in the Crnica River (Vranković et al, 2018). Additionally, study of Duman and Kar (2015) supports our results with the conclusion that GPx enzyme is the first-line antioxidant defense enzyme in Gammarus pulex. Significant seasonal variation in the activity of GPx was observed only at SK2 locality, with a large decrease in summer, followed by a gradual but incomplete recovery toward winter (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Similar high sensitivity of GPx to trout farm pollution was observed in Gammarus dulensis in the Crnica River (Vranković et al, 2018). Additionally, study of Duman and Kar (2015) supports our results with the conclusion that GPx enzyme is the first-line antioxidant defense enzyme in Gammarus pulex. Significant seasonal variation in the activity of GPx was observed only at SK2 locality, with a large decrease in summer, followed by a gradual but incomplete recovery toward winter (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, lead can produce physiological stress and induce the production of superoxide anion (O 2 •−) and hydrogen peroxide (H 2 O 2 ) in perennial ryegrass [30], which are harmful to plant cells. Plants can produce antioxidant enzymes to reduce the oxidative stress and maintain the resistance against heavy metals [37]. The current results show that soil inoculation with strain Act12 increased leaf CAT, SOD and POD activities in ryegrass plants under Pb stress compared with the un inoculated control.…”
Section: Lead Bioavailability In Soil and Pb Accumulation And Uptake mentioning
confidence: 53%
“…The activities of the three enzymes markedly increased in inoculated plants grown in soil at higher Pb levels (500-1,000 mg kg -1 ). SOD can convert active and toxic superoxide radical into H 2 O 2 ; CAT and POD then eliminate H 2 O 2 through the conversion to H 2 O and O 2 [37]. Improving the antioxidant enzyme activity thus can increase the detoxification of heavy metal stress by plants [38].…”
Section: Lead Bioavailability In Soil and Pb Accumulation And Uptake mentioning
confidence: 99%
“…Our findings support the results of Wang and Wang [41] who reported similar results in Tigriopus japonicus copepod exposed to 100 μg/L of Cd. The increase in lipid peroxidation is also observed in Gammarus pulex after 32 μg/L of Cd exposure [42] . Li et al [40] have demonstrated that the MDA contents increase with exposure time and dose and show time and dose-dependency in Crab Sinopotamon henanense exposed to Cd.…”
Section: Discussionmentioning
confidence: 75%
“…These findings are in accordance with Lei et al [45] who notes that CAT activity is increased in freshwater crab Sinopotamon yangtsekiense exposes to Cd on day 5 and decreases with increasing Cd concentration and exposure time. Similarly, study conducted on Gammarus pulex , that are exposed to Cd and assessed for antioxidant stress activity shows that the activity of CAT increases for 48 h. However, a decrease is observed compared with the control group and the authors claimed that CAT is the first enzyme to respond to oxidative stress [42] .…”
Section: Discussionmentioning
confidence: 98%